To analyze Consumer Satisfaction level in Digital Content Marketing with Emphasis on Shopping Websites - Khandelwal, Manvi; Sharma, Ashok; Deepika Varshney, Deepika; Arti Dagur, Arti (International Journal of Engineering and Technology, 2018)
It has been in trend that all the content is designed according to the customerâ€™s need and which provides some kind of information that can benefit a customer. In this research, an effort has been made for understanding the use and importance of digital content marketing strategy deployed by companies/ websites to gain new customers and securing the key customers, evaluating the content marketing factors which are responsible for the consumerâ€™s buying behavior and analyzing their satisfaction are the main objectives. People living in Delhi NCR were taken as samples and the framework of the structured questionnaire examined content marketing factors which nowadays companies acquired to increase their sales growth and market value. Questionnaire was divided into 3 parts: Demographic Profiles of the respondents, Content Profile includes all the factors which are essential to make content of a website more reliable and effective and the last phase is satisfaction profile which examines the satisfactory score of the consumers while preferring a particular website to shop online great content can also determine the level of sales. The results, were analyzed and it emerged that digital content marketing has a high significant impact on customers, and it is an important marketing tool type which cannot be ignored by websites or companies. Content marketing strategy should include some feature which can help to gain more satisfaction are properly designed in terms of spacing, language, edit cart feature, security logo display, offers and discount should be available on special occasions and festivals, feedback and review display for each product, live chat option service for 24*7 times, accurate and reliable information about the product should be on website. Customer satisfaction level was measured in terms of brand education, financial benefit and recommendation.Â Â